Penerapan Hukum Undang-Undang Ketenagakerjaan Nomor 13 Tahun 2003 Terhadap Penjatuhan Pemberian Pesangon Bagi Karyawan (Studi Putusan Nomor 124/G/2011/PHI.Mdn) - Noni Zulkarnain; Taufik Siregar; Sri Hidayani (JUNCTO: Jurnal Ilmiah Hukum, 2021)
Labor has a very important position as actors and objectives of development, therefore all activities carried out by workers will contain aspects of social relations, legal relations, interm organizational relationships that give rise to rights and obligations and are carried out based on the values contained in Pancasila. One of the problems in labor is Industrial Relations Disputes. One of the problems in industrial relations disputes is Termination of Employment. Termination of employment, according to Law Number 13 Year 2003 concerning Manpower Article 1 paragraph 25, the definition is the termination of a work relationship due to certain matters resulting in the termination of rights and obligations between workers / laborers and entrepreneurs. This research uses normative juridical research and analytical descriptive research. The techniques used in data collection through library research and field research. Layoffs are not only factored by employers / employers, there are several other factors that influence including factors from the workers / laborers. It is also undeniable that the process of terminating employment has constraints and obstacles based on the employer / employer, worker / laborer and also the Industrial Relations Settlement institution.